Canine Subcutaneous Mast Cell Tumors: Cellular Proliferation and KIT Expression as Prognostic Indices - Thompson, J. J.; Yager, J. A.; Best, S. J.; Pearl, D. L.; Coomber, B. L.; Torres, R. N. [UNESP]; Kiupel, M.; Foster, R. A. (Sage Publications Inc, 2011)
Molecular assays are widely used to prognosticate canine cutaneous mast cell tumors (MCT). There is limited information about these prognostic assays used on MCT that arise in the subcutis. The aims of this study were to evaluate the utility of KIT immunohistochemical labeling pattern, c-KIT mutational status (presence of internal tandem duplications in exon 11), and proliferation markers-including mitotic index, Ki67, and argyrophilic nucleolar organizing regions (AgNOR)-as independent prognostic markers for local recurrence and/or metastasis in canine subcutaneous MCT. A case-control design was used to analyze 60 subcutaneous MCT from 60 dogs, consisting of 24 dogs with subsequent local recurrence and 12 dogs with metastasis, as compared to dogs matched by breed, age, and sex with subcutaneous MCT that did not experience these events. Mitotic index, Ki67, the combination of Ki67 and AgNOR, and KIT cellular localization pattern were significantly associated with local recurrence and metastasis, thereby demonstrating their prognostic value for subcutaneous MCT. No internal tandem duplication mutations were detected in exon 11 of c-KIT in any tumors. Because c-KIT mutations have been demonstrated in only 20 to 30% of cutaneous MCT and primarily in tumors of higher grade, the number of subcutaneous MCT analyzed in this study may be insufficient to draw conclusions on the role c-KIT mutations in these tumors.
Keywords: AgNOR; canine; case-control study; c-KIT; Ki67; mast cell tumor; mitotic index; prognostic markers